1984
DOI: 10.1007/bf00165157
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic benefits of combination chemotherapy with vincristine, BCNU, and procarbazine on recurrent cystic craniopharyngioma

Abstract: The authors report a case of recurrent cystic craniopharyngioma managed with chemotherapy. The patient refused adamantly the alternative therapy methods, such as surgery and radiotherapy, initially offered. Eight courses of chemotherapy with vincristine (2 mg/M2, i.v.) on day 1,1,3-bis(2-chloroethyl)-1-nitrosourea (100 mg/M2, i.v.) on day 2, and procarbazine (50 mg, b.i.d., p.o.) on days 3 to 21 were administered at 6 week intervals. The effectiveness of this treatment modality has been evaluated by the unequi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

1988
1988
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…Complications of intralesional chemotherapeutic treatment have been reported to be associated with the toxic effects of bleomycin on the hypothalamus, 48 as in a case in which, after intracystic injection of bleomycin, a patient developed hypersomnia, personality changes, memory impairment, and thermal dysfunction. Bremer, et al, 14 have reported finding neurological improvement and decreased cyst size following systemic combination treatment with vincristine, carmustine (BCNU), and procarbazine.…”
Section: Neurosurg Focus / Volume 12 / May 2002mentioning
confidence: 99%
“…Complications of intralesional chemotherapeutic treatment have been reported to be associated with the toxic effects of bleomycin on the hypothalamus, 48 as in a case in which, after intracystic injection of bleomycin, a patient developed hypersomnia, personality changes, memory impairment, and thermal dysfunction. Bremer, et al, 14 have reported finding neurological improvement and decreased cyst size following systemic combination treatment with vincristine, carmustine (BCNU), and procarbazine.…”
Section: Neurosurg Focus / Volume 12 / May 2002mentioning
confidence: 99%
“…Bremer et al treated a case of cystic craniopharyngioma with systemic chemotherapy using the combination of vincristine, carmustine and procarbazine, resulting in tumor shrinkage and clinical improvement [22]. Lippens et al reported four cases of adamantinomatous craniopharyngioma with multiple recurrences after several surgical procedures and RT.…”
Section: Discussionmentioning
confidence: 98%
“…Significant and persistent reduction in tumour size has been recorded in response to systemic therapy with BCNU, vineristine and procarbazine in combination (Bremer et al, 1984) and to nitrogen mustard, vineristine, procarbazine and prednisolone in combination (Fischer et al, 1990). Responses to intracavitary methotrexate (Constine et al, 1989) and to bleomycin (Broggi et al, 1989) have been observed and in one series seven children with cystic craniopharyngiomas showed durable responses to intracyst bleomycin given as the primary treatment (Takahashi et al, 1985).…”
Section: Radiation Therapymentioning
confidence: 96%